2017
DOI: 10.1186/s13014-017-0772-5
|View full text |Cite
|
Sign up to set email alerts
|

Is pulmonary artery a dose-limiting organ at risk in non-small cell lung cancer patients treated with definitive radiotherapy?

Abstract: PurposeOur previous study suggested that some pulmonary artery (PA) dosimetric parameters were associated with mortality in unresectable non-small cell lung cancer (NSCLC) treated with definitive radiotherapy. The present study aims to analyze the impact of both PA and heart dosimetric parameters on survival of patients with NSCLC treated with definitive conventional fractionated radiotherapy (CFRT) in another independent research center and further determine whether the PA should be considered a dose-limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Figure 2 reveals the different cardiac substructures that have been found to be significantly associated with cardiac events or mortality in patients having radical radiotherapy for lung cancer. 20 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 A number of studies point to dose received by cardiac substructures at the base of the heart as being associated with reduced survival or cardiac events. The base of the heart is defined anatomically as posterior to the sternum, at the level of the third costal cartilage.…”
Section: Limiting Dose To Cardiac Substructuresmentioning
confidence: 99%
“…Figure 2 reveals the different cardiac substructures that have been found to be significantly associated with cardiac events or mortality in patients having radical radiotherapy for lung cancer. 20 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 A number of studies point to dose received by cardiac substructures at the base of the heart as being associated with reduced survival or cardiac events. The base of the heart is defined anatomically as posterior to the sternum, at the level of the third costal cartilage.…”
Section: Limiting Dose To Cardiac Substructuresmentioning
confidence: 99%
“…1 Additional publications that followed the reporting of RTOG 0617 have explored retrospective and clinical trial data to develop a better understanding of the influence of cardiac dose on overall survival after radiation therapy. [2][3][4][5][6][7][8][9][10][11][12][13] A pooled analysis of 112 patients with NSCLC in clinical trials identified heart mean dose as being independently associated with cardiac events after treatment. Cardiac events were observed in 23% of the patients for whom the mean dose to the heart was identified as a predictor in multivariable analysis, including correcting for baseline cardiac risk.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of a cardiac event for patients with a mean heart dose of <10 Gy, 10 to 20 Gy, or >20 Gy was 4%, 7%, and 21%, respectively, adjusted for competing risk. 13 Retrospective analyses have highlighted the V40-55 dose to pulmonary artery 9 and high dose to the left atrium and superior vena cava 3 as being associated with early mortality. In addition, changes in electrocardiograms (ECGs) were observed owing to the large dose to the left atrial wall.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the results from RTOG 0617 showed radiation dose to the heart, in lung cancer patients, was associated with worse overall survival [1] . Since the publication of RTOG 0617 a number of papers have further analysed the impact of cardiac dose, with the majority of these papers analysing retrospective datasets from a single institution or data from clinical trials [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . These studies were summarised in the 2019 review by Zhang et al [14] , which concluded that no consistent cardiac dosimetric parameters yet exist.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the literature [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] investigates dose to cardiac volumes, where some sub-structures are located primarily on the surface of the heart. The coronary arteries originate from the ascending aorta and are located across the surface of the heart.…”
Section: Introductionmentioning
confidence: 99%